Taphonomic and zooarchaeological investigations at the middle Pleistocene site of Ti's al Ghadah, western Nefud Desert, Saudi Arabia. (15th August 2019) - Stewart, Mathew; Louys, Julien; Groucutt, Huw S.; Candy, Ian; Clark-Wilson, Richard; Breeze, Paul S.; Drake, Nick A.; Price, Gilbert J.; Al-Mufarreh, Yahya S.A.; Soubhi, Saleh A.; Zalmout, Iyad S.; Alsharekh, Abdullah M.; et al.
Abstract: In recent years, the Arabian Peninsula has emerged as a key region for elucidating hominin and faunal evolution and dispersals between Africa and Eurasia. Central to this research is the middle Pleistocene site of Ti's al Ghadah (TAG) which has yielded a diverse and abundant fossil faunal assemblage and the earliest chronometrically dated evidence for hominins in this part of the world. Here, we present the first detailed taphonomic study of the large Unit 5 fossil assemblage from the site. We aim to assess which actor/s were responsible for the accumulation of the assemblage and evaluate evidence that might be consistent with the accumulation of fauna by hominins. We also describe, for the first time, fossils and lithic artefacts from stratigraphic horizons not previously considered, providing taphonomic insights into their accumulation. The taphonomic work shows that the Unit 5 faunal assemblage was accumulated by ambush predators, likely large felids and hominins, in a lake side environment, and that carcasses were subsequently scavenged by more durophagus carnivores such as hyenas and canids. Less can be reliably said regarding the newly described fossil assemblages given their poor preservation and significant wind abrasion, but large carnivores again appear to have played a role, and hominins probably played a role in the accumulation of at least one of these. This study provides the first detail insights into the interplay between hominins, carnivores, and herbivores in Arabia, and suggests that watering holes have been a focus on the Arabian landscape for resources since the middle Pleistocene. Highlights: First taphonomic analysis of the middle Pleistocene Ti's al Ghadah fossil assemblage. Large felids, and probably hominins, ambushed prey in a lakeside setting. Carnivores such as hyenas and canids subsequently scavenged carcasses. First insights into hominin-animal interactions in the Pleistocene of Arabia.